2019
DOI: 10.1002/cpdd.654
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase I Trial to Evaluate the Safety, Tolerability, Pharmacokinetics, and Pharmacodynamics of Topical Daprodustat in Healthy Volunteers and in Patients With Diabetic Foot Ulcers

Abstract: Daprodustat, a small‐molecule inhibitor of prolyl hydroxylases, prevents breakdown of hypoxia‐inducible factor (HIF), leading to increased transcription of HIF‐responsive genes. This randomized, placebo‐controlled study evaluated the safety, tolerability, and pharmacokinetics of a topical formulation of daprodustat in healthy volunteers (intact skin) and in patients with diabetic foot ulcers (DFUs) following single and/or 14‐day repeat‐dose administration. In the diabetic patients, exploratory assessments of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Stabilization of HIF-1α has been widely reported to be a critical factor in the improvement of wound healing ( Zhu et al, 2020 ). Olson et al (2019) reported improvements in wound healing by evaluating the wound area, volume and depth in daprodustat topical formulation-treated healthy volunteers with intact skin and diabetic foot ulcer patients and the mechanism was illustrated by activation of HIF-1 signaling and promoted vascularization. Zhu et al (2019) reported a similar effect of roxadustat on wound healing in diabetic rats.…”
Section: Potential Appliance Of Hif-phds Inhibitors In Non-anemic Dis...mentioning
confidence: 99%
“…Stabilization of HIF-1α has been widely reported to be a critical factor in the improvement of wound healing ( Zhu et al, 2020 ). Olson et al (2019) reported improvements in wound healing by evaluating the wound area, volume and depth in daprodustat topical formulation-treated healthy volunteers with intact skin and diabetic foot ulcer patients and the mechanism was illustrated by activation of HIF-1 signaling and promoted vascularization. Zhu et al (2019) reported a similar effect of roxadustat on wound healing in diabetic rats.…”
Section: Potential Appliance Of Hif-phds Inhibitors In Non-anemic Dis...mentioning
confidence: 99%